2022
DOI: 10.3389/fmed.2022.787167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Safety Between Standard, Accelerated Epithelium-Off and Transepithelial Corneal Collagen Crosslinking in Pediatric Keratoconus: A Meta-Analysis

Abstract: PurposeThe purpose of the study is to compare the efficacy of standard epithelium-off CXL (SCXL), accelerated epithelium-off CXL (ACXL), and transepithelial crosslinking CXL (TECXL) for pediatric keratoconus.MethodsA literature search on the efficacy of SCXL, ACXL, and TECXL [including accelerated TECXL (A-TECXL)] for keratoconus patients younger than 18 years was conducted using PubMed, Cochrane Library, ClinicalTrials.gov, and EMBASE up to 2021. Primary outcomes were changes in uncorrected visual acuity (UCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…In agreement with our results Dervenis et al, 17 aimed to compare the depth of the demarcation line developing in the cornea after the standard Dresden protocol versus the accelerated, pulsed, epithelium-off corneal collagen cross-linking (CXL), and found that the demarcation line postoperatively was deeper in the conventional group than accelerated group but without statistical significance as well as Kmax was non-significantly differed between the studied groups. In contrast to our results, Eissa & Yassin, 11 reported that Pentacam-measured Kmax during the last follow-up visit at 36 months post-CXL indicated a statistically significant difference (P< 0.05) between the two groups, with a statistically significant reduction in steepest K in the accelerated CXL group.…”
Section: Resultssupporting
confidence: 90%
“…In agreement with our results Dervenis et al, 17 aimed to compare the depth of the demarcation line developing in the cornea after the standard Dresden protocol versus the accelerated, pulsed, epithelium-off corneal collagen cross-linking (CXL), and found that the demarcation line postoperatively was deeper in the conventional group than accelerated group but without statistical significance as well as Kmax was non-significantly differed between the studied groups. In contrast to our results, Eissa & Yassin, 11 reported that Pentacam-measured Kmax during the last follow-up visit at 36 months post-CXL indicated a statistically significant difference (P< 0.05) between the two groups, with a statistically significant reduction in steepest K in the accelerated CXL group.…”
Section: Resultssupporting
confidence: 90%